Local Knowledge in households and communities management : Case study of Ban Na Nge, Nareng sub-district Noppitum district, Nakhon Si Thammarat province - Nillakan, Lunjakon (Ratchaphruek Journal, 2020)
Wisdom in management of households and communities in the case of Ban Na Ngae, Na Rong Subdistrict, Nop Phitam District, Nakhon Si Thammarat Province. Its objectives are to study (1) the learning process, analytical methods, wisdom usage, management of households and communities, (2) the factors of development of wisdom, management of household and community ways. Key informant is the person who learn in the community. Seven participants are community leaders and community directors who have experiences in applying wisdom to manage households and communities. Occurrences Interview with Focus Group Discussions Analysis from Focus group Analysis and theoretical analysis are collected. The results revealed that the learning process of managing local knowledge of households and community management stemmed from their leader who is a knowledge enthusiast about bringing local knowledge into the use within groups of 3 main factors which are: 1) Community leader is a respected person and yearn for knowledge as well as willing to sacrifice for the good of the community, 2) Faith and beliefs are the core of group activities which drives cultural and recreational community activities, and 3) Development of the community’s economy by employing local knowledge to increase income and advances careers for households and the community.